EVALUASI KINERJA HEAT EXCHANGER DENGAN METODE FOULING F - Bambang Setyoko (Diponegoro University, 2008)
The performance of heat exchangers usually deteriorates with time as a result of accumulation of depositson heat transfer surfaces. The layer of deposits represents additional resistance to heat transfer and causesthe rate of heat transfer in a heat exchanger to decrease. The net effect of these accumulations on heattransfer is represented by a fouling factor Rf , which is a measure of the thermal resistance introduced byfouling.In this case, the type of fouling is the precipitation of solid deposits in a fluid on the heat transfer surface.The mineral deposits forming on the inner and the outer surfaces of fine tubes in the heat exchanger. Thefouling factor is increases with time as the solid deposits build up on the heat exchanger surface. Foulingincreases with increasing temperature and decreasing velocity.In this research, we obtain the coefisien clean overal 5,93 BTU/h.ft2.oF, Dirt factor 0,004 BTU/h.ft2 0F,Pressure drope in tube 2,84 . 10-3 Psi and pressure drope in shell 4,93 . 10-4 Psi.This result are less thanthe standard of parameter. Its means this Heat exchanger still clean relativity and can operate continousslywithout cleaning.